2012
DOI: 10.1007/s00221-012-3242-1
|View full text |Cite
|
Sign up to set email alerts
|

Keeping your balance while balancing a cylinder: interaction between postural and voluntary goals

Abstract: The present study investigated whether postural responses are influenced by the stability constraint of a voluntary, manual task. We also examined how task constraint and first experience (the condition with which the participants started the experiment) influence the kinematic strategies used to simultaneously accomplish a postural response and a voluntary task. Twelve healthy older adults were perturbed during standing, while holding a tray with a cylinder placed with the flat side down (low constraint; LC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
2
7
0
8
Order By: Relevance
“…They found that subjects used a characteristic control strategy in each condition; interestingly, they also found that when subjects transferred from one condition to the other, they initially used an intermediate control strategy before adapting the characteristic strategy of the new condition. In two other studies, de and Papegaaij et al (2012) studied the effects of voluntary task stability constraints on reactive postural control. Subjects stood on a platform and held a tray (voluntary task) with a half-cylinder placed flat side down (low stability constraint) or round side down (high stability constraint) and were perturbed with backward surface translations (postural task).…”
Section: Transfer Of Postural Controlmentioning
confidence: 99%
“…They found that subjects used a characteristic control strategy in each condition; interestingly, they also found that when subjects transferred from one condition to the other, they initially used an intermediate control strategy before adapting the characteristic strategy of the new condition. In two other studies, de and Papegaaij et al (2012) studied the effects of voluntary task stability constraints on reactive postural control. Subjects stood on a platform and held a tray (voluntary task) with a half-cylinder placed flat side down (low stability constraint) or round side down (high stability constraint) and were perturbed with backward surface translations (postural task).…”
Section: Transfer Of Postural Controlmentioning
confidence: 99%
“…In conclusion, as Trivedi et al (2010) and Papegaaij et al (2012) have also demonstrated, we have shown that a significant interaction between the feed-forward adjustments of posture required to complete a reach movement while standing and the feedback adjustments of posture needed to correct for an unexpected perturbation. This study has provided further evidence, however, that the precise nature of this interaction depends upon body-target interaction with both target reference frame and time of platform perturbation playing a significant role in the modulation of postural activity.…”
Section: Perturbations Given During Reaching Movements Results In Diffmentioning
confidence: 66%
“…É provável que a avaliação do centro de pressão realizada não seja uma medida sensível para ser utilizada em estudos com este tipo de perturbação de equilíbrio. No estudo realizado por Papegaaij et al (2012) também se verificou uma situação em que as diferenças verificadas em termos musculares, entre as condições de alta e baixa restrição, não se refletiram em modificações importantes do centro de pressão ou do centro de massa .…”
Section: Desempenho Na Tarefa Cognitivaunclassified